A simple switching on-time calculation revision in multilevel inverter-space vector modulation to achieving extended voltage boundary operation - Bharatiraja C.; R.K. Pongiannan; Adedayo Yusuff; Mohd Tariq; Telugu Maddileti; Tharwinkumar Tharwinkumar (Institute of Advanced Engineering and Science, 2019)
In inverters’ pulse width modulation techniques (PWM) the Space Vector PWM (SVPWM) is a smart contestant due to its direct control in nature with variables which provide the straight forward finds to each inverter switching vector. The industrial drives are acquainting to use SVPWM owing extended speed –torque region operations. However, the extended SVPWM operation is uses much mathematical calculation to predict the switching on-times, which demands high digital platform. In order to reduce this calculation in this paper a simple on-time calculation based SVPWM is proposed. The proposed SVPWM is developed for three-level multilevel inverter and the space perspective of vector analysis are established and explained. The over modulation enhances the proper power utilization capacity of voltage source inverter thereby improve the inverter output voltage and load. This proposed method tailed the similar mathematical practice as conventional two-level SVPWM for calculating sector identification and triangle determination. The approach finds the circular and hexagonal boundary on-time based on the straightforward reference vector position identification and calculates directly the switching pulse patterns for the inverter devices using an expression based on the definition of the duty cycle. The performance of the proposed SVM is simulated by MATLAB 11.b simulation software and validated with laboratory setup 2 kW, 12 switch neutral point clamped (NPC)-MLI fed 1.5 HP squirrel cage 3-phase induction motor open loop v/f control drive. The simulation and experimental results are closure and confirming the advantages of the proposed SVM method. The proposed scheme can be extended to n-level inverter and also applicable to cascaded H-bridge topology.